Transformasi Absensi Berbasis Automasi dalam Meningkatkan Kedisiplinan Siswa - Siti Nurjanah; Iwan Sopwandin (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the transformation of attendance from manual to automation and its management process at Madrasah Ibtidaiyah Negeri 2 Tasikmalaya in improving student discipline. This study is included in the type of qualitative research with a data collection process through participant observation, semi-structured interviews, and documentation studies. The data analysis technique is through data condensation, data presentation and drawing conclusions. Meanwhile, the data validity test is carried out by extending observations, triangulation, peer review, reference adequacy, and member checks. The results of this study indicate that the activities carried out in the use of automated attendance include: 1) planning involving class teachers, BK teachers and the Head of Madrasah. The things that are prepared include student discipline programs and devices used in this case android, google form and QR Code; 2) The implementation of attendance automation at Madrasah Ibtidaiyah Negeri 2 Tasikmalaya is carried out through a prepared pattern; 3) Supervision in the use of automated attendance is carried out in a structured manner. The use of automated attendance has a significant impact on the development and progress of Madrasah Ibtidaiyah Negeri 2 Tasikmalaya, especially in student discipline.